Teacher-class relationship and emotional intelligence in the academic output and generic competence of higher education students. - Rahat Yasmeen; Ashfaque Ahmad Shah; Sehrish Naseer; Zunaira Fatima Syeda (PLoS ONE, 2023)
Academic output of students is considered as a crucial element and it is affected by various aspects. Teacher-class relationship, emotional intelligence and generic competence are the elements which can have a considerable effect on the academic output of the students. Current study was intended to find out the moderating role of teacher-class relationship, emotional intelligence in the academic output and generic competence of higher education students. All the teachers and students of University of Sargodha were the population of the study. The sample was taken from four departments of different faculties of University of Sargodha i.e., Faculty of Agriculture, Faculty of Medical and Health Sciences, Faculty of Arts and Humanities and Faculty of Social Sciences. For this study, a sample of 21 teachers and 320 students from regular and self-support programs was selected conveniently from University of Sargodha. For data collection, three adapted instruments were used. Findings of current study concluded an insignificant moderating role of teacher-class relationship and emotional intelligence in the academic output and generic competence of students at higher education. The results of present study provide guideline to curriculum developers for developing the generic competence of students so that they can progress in future prospects which will eventually make contribution towards economy, moreover, stakeholder may take steps in order to develop the emotional intelligence of students by providing them needful counseling and trainings which will improve the academic output of students.